1998
DOI: 10.1097/00000374-199802000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Neural Crest Apoptosis Is Coincident with Their Endogenous Death, But Is Mechanistically Distinct

Abstract: The ability of both acute and chronic ethanol exposures to elicit cell death within specific embryonic and adult tissues is believed to partly underlie ethanol's pathogenicity; however, the mechanism underlying this cell death is unknown. This study partially characterized the mechanism of ethanol-induced neural crest cell death in a chick embryo model of fetal alcohol syndrome. In situ DNA end-labeling demonstrated this cell death was apoptotic and occurred at embryonic ethanol levels as low as 42 mM. Regardl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 1 publication
5
76
2
Order By: Relevance
“…However, the same studies by Miller and colleagues reported an overall loss of cortical neurons postnatally. A recent report also indicated decreased number of GABAergic cells in the adult guinea pig and rat cortices (Moore et al, 1998;Bailey et al, 2004), an effect that could be attributed to ethanol inducing apoptosis (Bhave and Hoffman, 1997;Cartwright et al, 1998;Cheema et al, 2000;Dikranian et al, 2005). The discrepant results could be reconciled by hypothesizing cell death occurring in the immature cortex later than E14.5, including early postnatal ages, that is exacerbated by gestational ethanol.…”
Section: Discussionmentioning
confidence: 98%
“…However, the same studies by Miller and colleagues reported an overall loss of cortical neurons postnatally. A recent report also indicated decreased number of GABAergic cells in the adult guinea pig and rat cortices (Moore et al, 1998;Bailey et al, 2004), an effect that could be attributed to ethanol inducing apoptosis (Bhave and Hoffman, 1997;Cartwright et al, 1998;Cheema et al, 2000;Dikranian et al, 2005). The discrepant results could be reconciled by hypothesizing cell death occurring in the immature cortex later than E14.5, including early postnatal ages, that is exacerbated by gestational ethanol.…”
Section: Discussionmentioning
confidence: 98%
“…Although these authors suggested that dysmorphology of the glossopharyngeal and vagus cranial nerves may be attributed to ethanol's effects on neural crest cells derived from r6 and r7, the pathogenesis for these anomalies was never experimentally confirmed. Work from our laboratory [Kotch and Sulik, 1992;Dunty et al, 2001] and others [Cartwright and Smith, 1995a, b;Cartwright et al, 1998] has shown that highly migratory cell populations, such as the neural crest, are very sensitive to ethanol exposure during embryogenesis. It is likely that abnormalities of the proximal sensory ganglia noted in both the current in vivo and previous in vitro study [Van Maele-Fabry et al, 1995] are a result of a direct insult to this precursor cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal ethanol exposure during a crucial developmental period in the rat (gestational day [GD] 6 to birth) leads to a significant decrease in the number of neurons generated during the peak period of neurogenesis (Miller, 1988), and consequently, a decreased neuron number in the mature cortex (Miller and Potempa, 1990). This cell loss has largely been attributed to the ability of ethanol to induce apoptosis (Bhave and Hoffman, 1997;Cartwright et al, 1998;Bhave et al, 1999;Cheema et al, 1999;McAlhany et al, 2000;Ramachandran et al, 2003;Young et al, 2003;Takadera and Ohyashiki, 2004;Dikranian et al, 2005). Although we know that ethanol can induce apoptosis of fetal cortical neurons in late gestation (Ramachandran et al, 2003), relatively few studies (Kentroti and Vernadakis, 1991;Hao et al, 2003;Santillano et al, 2005) have focused on the apoptotic effects of ethanol on embryonic neural progenitors during early neurogenesis.…”
Section: Introductionmentioning
confidence: 99%